Functional Antagonism of Human CD40 Achieved by Targeting a Unique Species-Specific Epitope. Issue 14 (17th July 2016) - Yamniuk, Aaron P.; Suri, Anish; Krystek, Stanley R.; Tamura, James; Ramamurthy, Vidhyashankar; Kuhn, Robert; Carroll, Karen; Fleener, Catherine; Ryseck, Rolf; Cheng, Lin; An, Yongmi; Drew, Philip; et al.
Abstract: Current clinical anti-CD40 biologic agents include both antagonist molecules for the treatment of autoimmune diseases and agonist molecules for immuno-oncology, yet the relationship between CD40 epitope and these opposing biological outcomes is not well defined. This report describes the identification of potent antagonist domain antibodies (dAbs) that bind to a novel human CD40-specific epitope that is divergent in the CD40 of nonhuman primates. A similarly selected anti-cynomolgus CD40 dAb recognizing the homologous epitope is also a potent antagonist. Mutagenesis, biochemical, and X-ray crystallography studies demonstrate that the epitope is distinct from that of CD40 agonists. Both the human-specific and cynomolgus-specific molecules remain pure antagonists even when formatted as bivalent Fc-fusion proteins, making this an attractive therapeutic format for targeting hCD40 in autoimmune indications. Graphical Abstract: Highlights: Can agonist and antagonist activities be separated for CD40 therapeutic agents? dAbs identified with unique human-specific antagonist epitope. X-ray crystal structures show molecular details of dAb and antibody epitopes. Cynomolgus-specific surrogate dAb molecules generated, also potent antagonist dAbs targeted to unique epitope are functional antagonists as bivalent Fc-fusion.